3D BiOI–GO composite with enhanced photocatalytic performance for phenol degradation under visible-light. Issue 3 (April 2015) - He, Rongan; Cao, Shaowen; Guo, Daipeng; Cheng, Bei; Wageh, S.; Al-Ghamdi, Ahmed A.; Yu, Jiaguo
Abstract: Coupling semiconductors with graphene-based materials could enable better photocatalytic performance as compared to that of pristine semiconductors. In this work, a three-dimensional BiOI–GO composite was fabricated by a simple self-assembly approach. The resultant BiOI–GO composite showed a higher photocatalytic activity than that of pure BiOI and P25 towards the degradation of phenol under visible-light irradiation, which could be attributed to the more effective separation of photogenerated electrons and holes between BiOI and GO, and the better adsorption capacity of phenol.